"Doctor my eyes": A natural experiment on the demand for eye care services. (February 2016) - Dickey, H.; Ikenwilo, D.; Norwood, P.; Watson, V.; Zangelidis, A.
Abstract: Preventive health care is promoted by many organisations from the World Health Organisation (WHO) to regional and national governments. The degree of cost-sharing between individuals and the health care service affects preventive service use. For instance, out-of-pocket fees that are paid by individuals for curative services reduce preventive care demand. We examine the impact of subsidised preventive care on demand. We motivate our analysis with a theoretical model of inter-temporal substitution in which individuals decide whether to have a health examination in period one and consequently whether to be treated if required in period two. We derive four testable hypotheses. We test these using the subsidised eye care policy introduced in Scotland in 2006. This provides a natural experiment that allows us to identify the effect of the policy on the demand for eye examinations. We also explore socio-economic differences in the response to the policy. The analysis is based on a sample from the British Household Panel Survey of 52, 613 observations of people, aged between 16 and 59 years, living in England and Scotland for the period 2001–2008. Using the difference-in-difference methodology, we find that on average the policy did not affect demand for eye examinations. We find that demand for eye examinations only increased among high income households, and consequently, inequalities in eye-care services demand have widened in Scotland since the introduction of the policy. Highlights: We examine the impact of subsidised eye examinations on eye care demand. We use the subsidised eye care policy in Scotland as a natural experiment. We argue that there is lack of significant impact on the number of eye examinations. Only higher income individuals increased their demand for eye examinations. Socioeconomic differences in the uptake widened inequalities in eye care demand.